History of E-Learning Development and Its Application in Learning - Ilham Muhamad Rizky (Konsultan Jurnal Ilmiah Indonesia, 2025)
E-learning is an electronic-based learning method or teaching and learning process conducted online, where various learning materials are delivered to users through the help of information technology. The purpose of this study is to determine the History of E-Learning Development and Its Application in Learning. The method used in this article is a qualitative research type with library research, namely research whose subjects are library literature. The data sources in this article depart from documentation originating from books and scientific journal articles that discuss the history of e-learning development and its application in learning. The results of this study are a learning platform to facilitate the learning process, the differences in e-learning between schools and universities are adjusted to the needs of certain educational institutions.